ANALISIS SUMBER DAN PENGGUNAAN DANA OPERASIONAL SEKOLAH DI SDN 10 KECAMATAN SEGEDONG KABUPATENMEMPAWAH - Fitriani, Fitriani; Ulfah, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This thesis is titled "Sources Analysis and Use of School Operational Funds in State Elementary Schools 10 Segedong Subdistrict, Mempawah Regency." The problem in this study is "What are the Sources and Uses of School Operational Funds in the 10 Elementary Schools in Segedong District, Mempawah? The method used is descriptive method. The data collection techniques used are direct communication techniques and documentary study techniques. Data collection tool uses interview guidelines and data contained in the archive owned. The results of this study 1) Source of funds for the School Operational Assistance program in the 10th Elementary School in Segedong District, Mempawah District. Based on the research findings or sources of funds for the School Operational Assistance Program in the State Elementary School in Segedong Subdistrict, Mempawah Regency, the source of education funding is all those who provide subsidies and donations received by the 10 institutions in Segedong Subdistrict, Mempawah Regency. Based on the findings of the School Operational Assistance Fund, used for school purposes. 3) The School Operational Assistance Program in Public Elementary School 10, Segedong Subdistrict, Mempawah Regency, runs in accordance with the corridor, the provisions that have been schooled, either from official sources or from the community itself. regular. 2) Used for whatever School Operational Assistance Funds in Public Elementary Schools are delivered first. All the implementation of the School Operational Assistance program in the Public Elementary School 10 in Segedong Subdistrict, Mempawah District, was realized in accordance with its operational instructions. And in the implementation involved the school committee inside.Â Keywords: Source and Use of School Operational Funds